(untitled) (Architecture Image Studies, 2025)
This study examined the Rating Practices of the RBPMS in public secondary schools of three divisions. Utilizing a descriptive research design, the study assessed the rating practices of RBPMS in the four phases, through the perspectives of public secondary teachers, master teachers, and head teachers. Respondents’ profiles were also analyzed based on their age, gender, civil status, highest educational attainment, length of service and position. Findings revealed that most respondents were experienced, married female educators aged 31–45, with pursuing graduate-level education. Findings indicated a high rating practices and satisfaction across the four RBPMS phases. Statistical analysis showed no significant differences in performance ratings across most demographic variables, although higher educational attainment and length of service were significantly associated in specific phases. Despite high implementation, several challenges were identified, including the lack of regular feedback, weak integration of performance with rewards, inadequate rater accountability, and low transparency. The study concluded that the RBPMS is implemented in terms of performance planning, monitoring, review, and rewards among teachers and instructional leaders. Even though it’s implemented, there were identified challenges such as feedback provision, accountability, transparency, and a reward system. Despite the demographic profile factors such as age, gender, civil status, and position showed no significant impact on performance ratings across the four phases, though higher educational attainment and length of service were linked to more favorable experiences in certain RBPMS phases. An improvement plan is proposed to address the findings and challenges encountered by the teachers and instructional leaders.